If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 = 2x + -3 Reorder the terms: 3 + 6x = 2x + -3 Reorder the terms: 3 + 6x = -3 + 2x Solving 3 + 6x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 6x + -2x = -3 + 2x + -2x Combine like terms: 6x + -2x = 4x 3 + 4x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 4x = -3 + 0 3 + 4x = -3 Add '-3' to each side of the equation. 3 + -3 + 4x = -3 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = -3 + -3 4x = -3 + -3 Combine like terms: -3 + -3 = -6 4x = -6 Divide each side by '4'. x = -1.5 Simplifying x = -1.5
| 2a+3a+5a-1=19 | | 4(1-7v)+3v= | | 7x-2(2x-3)=2.5(2x+4) | | 0.2=[10.0][20.0] | | 20x+15-100=130 | | 27z+108=0 | | 300x+20-150x=75 | | (6x+8)=(8x-2) | | x^2+y^2-8x+6y-5=0 | | 10x-15/2=75 | | 16x-15=9x-6 | | 17=3+7(x-5) | | since=1/3 | | 19x-23y=5 | | y=x^2+196 | | 35x+3=-17 | | x^2+300x-12.6=0 | | (24-x)-6=66 | | 9r^2+6r+4=0 | | x^2+300x-58=0 | | 6x-[6-5(3x+6)]= | | 2b=1+9 | | (x-x^2*y)*dy-y*dx=0 | | y=sqrt(x+2) | | 6y+96=180 | | -22-8n=5(-7-n) | | 5x(e+2)=25 | | 16x+16y+11+11x-2y-2= | | -8p=10-3p | | (8x^3-1)/(1-2x^3) | | -4(z-7)=24 | | 1.8x-2.2y-5.8x-5.7y= |